The Value of Nasal and Oral Clinical Examination in Febrile Neutropenic Patients for Initiating Antifungal Therapy as a Preemptive Method - Salehi, Mohammadreza; Ghaderkhani, Sara; Sharifian, Ramezan Ali; Dehghan Manshadi, Seyed Ali; Samiee Fard, Elahe; Khodavaisy, Sadegh; Pourahmad, Ramtin; Foroushani, Abbas Rahimi; Rodini, Kamran; Kamali Sarvestani, Hasti (Frontiers in Medicine, 2022)
Background Invasive fungal infections (IFIs) are complications that lead to mortality and morbidity in hematologic malignancies. The time of starting antifungal therapy is vital. Preemptive antifungal therapy has appeared recently as a new policy for the management of IFIs based on noninvasive ways in neutropenic patients. Methods We enrolled leukemia patients with neutropenia after chemotherapy in Imam Khomeini Hospital Complex, Tehran, Iran. Patients who entered the neutropenic phase were divided into two categories (empirical and preemptive) for receiving antifungal agents. The patients were clinically examined in the preemptive group every day to find IFIs. As soon as clinical evidence of IFIs was observed, antifungal was prescribed. The empirical group patients received antifungals based on the ward protocol. Based on the data in each group, the diagnostic and therapeutic results of cases are followed-up to 3 months. To compare percentages between the two groups, the chi-squared test was used. And to compare two means between the two groups, the independent t-test was used. All the statistical analyses were done in the Statistical Package for the Social Sciences (SPSS) version 24 software (IBM Corporation, Armonk, New York, USA). Results We assessed 132 leukemic patients with inclusion and exclusion criteria. Eventually, 80 patients were enrolled. The mean age was 35.52 years. Demographics data and distribution of leukemia type show no significant differences between the two groups. Despite a higher percentage of IFIs discovered in the preemptive group than the empirical group (25 vs. 18.75%, respectively), but data show no significant differences. The average days of IFIs diagnosis since the beginning of neutropenia in the empirical group were 9.5 days while in the preemptive group, the average days were 5.4 days (p < 0.05). Totally, there were 15 patients with a proven IFI in each group (40% in the empirical group and 60% in the preemptive group). Results significantly show an increase in surgical sinus debridement in the empirical groups (83.3%) vs. the preemptive groups (55.5%), (p < 0.05). The mortality rate differed significantly among the two groups; it was 7.5% in the preemptive group and 25% in the empirical group (p < 0.05). Conclusion Daily oral and nasal cavities examination to find the symptoms of IFIs and then start preemptive antifungal agents may be able to lead to accurate diagnosis, earlier treatment, and decreasing sinus surgery debridement in leukemia patients with neutropenia.